Olney São Paulo: maldição e esplendor em manhã cinzenta - Santos, Maria David (2013)
This work proposes a reading of the social, political, historical and cultural presents in the tale and movie called Manhã Cinzenta, 1966 and 1969 respectively, of Olney Alberto São Paulo (1936-1978). It was with the aim of discussing the reality of the country in his works, the writer and filmmaker early left his hometown of Riachão do Jacuípe, to live and acquire study in Feira de Santana, both cities in Bahia, where he developed activities related to theater, journalism and cinema. The "damn filmmaker backwoods" as well Olney São Paulo was known among friends, journalists and critics, brings this brand in his career because he has never produced a film shown commercially, and yet, the reason various surveys suffered during the military dictatorship in Brazil, the average film Manhã Cinzenta (1969). It is through this work that the memory of a remarkable period in the history of cinema and politics in Brazil is translated into moving images that convey an experience individual and collective, historical and fictional. In this sense, we present the relationship between fictional and documentary aspects of Manhã Cinzenta (1969), focusing on the discussion of cultural engagement in his narrative, marked by political tension, especially between the years 1968 to 1978 and the advent of censorship that came through its mechanisms of oppression and the author's work. Today, 34 years after the untimely death of Olney São Paulo, is both possible to recognize it as an important figure in the cultural landscape locally, nationally and internationally, as well as realize the erasure and forgetting about the contribution made by Olney São Paulo for Brazilian cinema of the twentieth century.